Девочка с перчиками: [роман] / Екатерина Вильмонт - Вильмонт Екатерина Николаевна (АСТ, 2011)
Экземпляры: Аб (20130315) / Инвентарный номер: 99462 / Цена: 156.00 / Авт.знак: В 46 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6